Next generation ICTs and their impact on consumer behaviour and marketing: are we ready? - CLAFFEY, ETHEL; Brady, Mairead (My University, 2006)
This paper seeks to provide an overview of some of the key attributes of next generation information and communication technologies (ICTs) that could directly impact on future consumer behaviour and by implication on marketing practice. While it would be an arduous exercise to attempt to categorise all next generation technologies that may impact on consumers, there is significant value in providing an overview of the attributes and characteristics of emerging technologies. A significant research effort is necessary to determine the impact these technologies could have on consumer behaviour, and how marketers may have to adapt their strategies to successfully compete to gain consumer confidence in this ever changing technical environment. This paper highlights the need for marketing academics and practitioners to consider more fully how advances in information and communication technologies (ICTs) are fundamentally changing the nature of consumer behaviour and how emerging technologies present a variety of new marketing options to organisations, both tactically and strategically.
PUBLISHED
Keywords: ICTs; Consumer Behaviour